KORO EĞİTİMİNDE DİL VARYASYONLARI VE YÖRESEL DİLİN ETKİLERİ - (:unkn) unknown (My University, 2017)
Bireylerin duygularını ve düşüncelerini ileten, ses, kelime ve cümlelerden oluşan somut bir iletişim aracı olan dil somut yapıya sahiptir. Bu yapı içinde işaretleri, beden ve yüz hareketlerini, yani jest ve mimikleri de taşır. Dil yalnızca iletişim aracı değil, bir ulusun geleneklerini, göreneklerini, hayat ve ötesi hakkındaki tasavvurlarını da içinde barındırır. Bu nedenle ünlü düşünür Haideger "Dil düşüncenin evidir" diyerek, düşünce sınırlarını aslında dilin sınırları olduğunu vurgular

As a concrete communication medium, language, which constitutes voice, words and sentences transferring an individual's emotions and ideas, has a concrete structure. This structure also transfers signs, body and face movements; in other words gestures and expressions. Language is not only a communication medium. It also includes a nation's customs, traditions, and visions of life and beyond. Therefore, the well-known philosopher Heidegger emphasises that the borders of ideas are actually the borders of the language, by saying "Language is the house of being". foundation of singing in choirs, is considered to be the common ground. Speaking built on this ground forms the foundation of singing. The common education received by individuals sustains the aim of actualisation of nationalism as unity in terms of both language and singing. Speaking voices and singing voices are different. However, in their formation they are identical with regards to air and language. Released air becomes a speaking voice by vibrating vocal cords and being affected by the shape and interaction of the organs inside the mouth. A singing voice is formed in the same way. However, stress used in the speaking voice and stress used in the singing voice is different. The way energy is accumulated and consumed is also different. Besides, there are only musical voices used in speaking, and these notes are next to each other- in other words, there is a graduated and wide-ranging structure. The singing voice is structured differently, and in this structure the musical statement is expressed. There may be very challenging parts. Furthermore, a singer or singers should have outstanding technical competence. Gathering and carrying out all these elements is only possible with the aid of long and detailed musical exercises. In class practices, there are exercises to develop a proper speaking voice. Additionally, with the help of rhymes, tongue twisters and voices, a connection between breathing and words can be made, and progress from good speaking to good singing can be made. Similarly it is planned to expand the voice, gain intonation and mobility (in voice), and to use voice pitch and accentuations in a much better way. Otacıoğlu ordered these elements to be taken note of in choir or solo voice education. In the language and speaking education which is a part of choir practices, eliminating all regional speaking differences and variations is a key aim. With this education, shaping standard language with correct breathing techniques and accentuations is targeted. The melodic structures needed to sing are the same in all languages. On the basis of this fact, these structures are studied to form a common and national singing tradition. The research we carried out will be crucial to generate solutions to the problems which are caused by different language usage in choir education
LANGUAGE VARIATIONS AND LOCAL LANGUAGE EFFECTS IN CHOIR EDUCATION
Keywords: Dil ve Dil Bilim